Direct and indirect effect of brand experience on true brand loyalty: role of involvement. Issue 3 (11th June 2018) - Mathew, Veeva; Thomas, Sam
Abstract : Purpose: The purpose of this paper is to investigate the role of product and customer dimensions in the contribution of brand experience to the formation of true brand loyalty. The dimensions included are brand credibility, affective commitment and involvement. Synthesising past studies, the researcher proposes brand credibility and affective commitment to mediate the relationship between brand experience and true brand loyalty. Furthermore, the researcher investigates the variation in hierarchical pattern, i.e. brand experience-brand credibility affective commitment-true brand loyalty, under different levels of involvement. Design/methodology/approach: The variations in hierarchy were compared by design. The authors investigated the variations in hierarchy on the basis of products which belong to different level of involvement, on the basis of individual differences in involvement, and on the basis of the interaction of product involvement and subject involvement. Multi-group invariance tests in SEM were used to explore model variations. Findings: The hierarchy-of-effect model was found to vary based on the level of product involvement, subject involvement and interaction involvement. Three patterns of hierarchy have been observed: the first pattern was observed in high-high groups (both product involvement and subject involvement were high), the second pattern was observed in low-low groups (both product and subject involvements were low) and the third pattern among high-low or low-high groups. Practical implications: The variation observed highlights the need to segment the market by interaction involvement. This would be useful for managers engaged in building sustainable consumer-brand relationships. Originality/value: This study considered the interaction of product approach and subject approach in defining involvement which is rarely attempted in research. The study also integrates the variations in the role of customer dimensions, namely involvement, brand credibility and affective commitment with the relationship between the central constructs brand experience and true brand loyalty. The variations observed are among a socio-economically homogeneous sample of respondents.